Highly photostable dye entrapped core-shell particles - Ethiraj, Anita S.; Kharrazi, Sharmin; Hebalkar, Neha; Urban, J.; Sainkar, S. R.; Kulkarni, S. K. (Materials Letters, 2007)
Organic dye namely Coumarin 7 has been entrapped in silica particles using a single silica precursor viz. tetraethylorthosilicate. Both bare Coumarin 7 dye and dye incorporated core-shell particles were studied. Investigations of these core-shell composites were carried out using different characterization techniques such as energy dispersive X-ray analysis, X-ray photoelectron spectroscopy and transmission electron microscopy. It has been shown that the photostability of dye molecules is improved along with an increase in photoluminescence. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: core-shell; coumarin 7 dye; Luminescence; photostability; tetraethylorthosilicate